Combined effects of alkaline pH and high Ca concentration on root morphology, cell-wall polysaccharide concentrations and blueberry plant performance - Tamir, Guy; Zeng, Qilong; Eli, Dagan; Zilkah, Shmuel; Bar-Tal, Asher; Dai, Nir (Frontiers in Agronomy, 2023)
The appropriate soil pH for blueberry production is <5.5. However, the exact factors involved in the retardation of blueberry growth at higher pH levels have not yet been completely identified. In this study, we examined the short- and long-term combined effects of pH level and Ca concentrations on root morphology and development in relation to blueberry plant performance. Southern highbush blueberry (Vaccinium corymbosum, cv. Windsor) plants were grown in solutions of pH 4.5 or 7.5 that contained 0, 5, 10, 50 or 100 mg L-1 of Ca. The dimensions of the epidermal cell walls of the roots and the levels of pectin and hemicellulose 1 and 2 in those cells were determined after 1 and 3 days. Concentrations of essential macro and micro-elements in the plant organs, chlorophyll concentrations in the leaves and whole-plant biomass production were measured after 12 weeks. The results demonstrate a rapid (3 days) negative response of root tips at pH 7.5 expressed as reduced dimensions and deformation of the epidermal cell walls. This response was accompanied by reduced concentrations of pectin and hemicellulose 1 in those cell walls. These negative effects of pH 7.5 were amplified by a 100 mg L-1 of Ca over the long term (12 weeks), where the the concentrations of P and Ca on the epidermal cell of the root were increased. Additionally, the translocation of Mn from the root to the shoot was retarded. The negative effect of the pH level on roots development and on the Mn translocation were associated with significant reductions in chlorophyll concentrations and biomass production. The results presented in this study demonstrate, for the first time, the negative effect of the combination of slightly alkaline pH and a high Ca concentration on root development, which associated with retarding blueberry plants performance.